Les élites sociales et le choix de l’enseignement français en Tunisie : Entre consumérisme scolaire et socialisation laïque - Émilie Pontanier (L’Année du Maghreb)
What are the strategies and expectations of Tunisian and French-Tunisian families who chose a French high school for their children? This research is about the various forms of social, cultural and religious distinctions these families are looking for and the strategies they undertake to meet them. Main aspects of these distinctions consist of the international recognition of French diplomas, the weight of language and culture or the wish for a secular socialisation. By putting their children in the French educational system, parents avoid their perceived dead ends of Tunisian state schools marked by arabisation and standardisation policies. They also involve their children in an institution that will bring in symbolic and material benefits, either on the national or international level, as the French educational system produces highly valued resources, which is a way to ensure social reproduction. These educational choices are also linked to secularism which is credited for enabling a world view with less strict forms of religion or even religious abstention. Thus, given the antagonism between religious and secular fields, students and parents in French high schools would privilege the latter to express their opinions. This population, mainly reluctant to religious fundamentalism, is looking to be different, culturally and religiously, through secular education.